2012
DOI: 10.1073/pnas.1200966109
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the phage TP901-1 1.8 MDa baseplate suggests an alternative host adhesion mechanism

Abstract: Phages of the Caudovirales order possess a tail that recognizes the host and ensures genome delivery upon infection. The X-ray structure of the approximately 1.8 MDa host adsorption device (baseplate) from the lactococcal phage TP901-1 shows that the receptor-binding proteins are pointing in the direction of the host, suggesting that this organelle is in a conformation ready for host adhesion. This result is in marked contrast with the lactococcal phage p2 situation, whose baseplate is known to undergo huge co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
249
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(258 citation statements)
references
References 31 publications
8
249
1
Order By: Relevance
“…In contrast, lactococcal phages of the 936 and P335 families seem to attach exclusively to polysaccharides and bear at their tail end a large macromolecular entity called the baseplate. The baseplate dimensions of phages p2 and TP901-1 are quite large, since these phages harbor a large number (18 to 54) of receptor binding proteins (RBPs), the specific proteins recognizing and attaching to the host (48,49). These baseplates have been found, to date, to be composed of a central axial core formed by Dit and Tal, shared with the straighttail tip phages (e.g., SPP1), and of a peripheral component formed by the RBPs as in phage p2 (49,71) and eventually other proteins as in phages TP901-1 (48,72) and Tuc2009 (73,74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, lactococcal phages of the 936 and P335 families seem to attach exclusively to polysaccharides and bear at their tail end a large macromolecular entity called the baseplate. The baseplate dimensions of phages p2 and TP901-1 are quite large, since these phages harbor a large number (18 to 54) of receptor binding proteins (RBPs), the specific proteins recognizing and attaching to the host (48,49). These baseplates have been found, to date, to be composed of a central axial core formed by Dit and Tal, shared with the straighttail tip phages (e.g., SPP1), and of a peripheral component formed by the RBPs as in phage p2 (49,71) and eventually other proteins as in phages TP901-1 (48,72) and Tuc2009 (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…HHpred searches revealed that the ORF protein following the TMP, ORF70, shares with ϳ80% probability structural similarity with the corresponding protein, Dit, in phage SPP1 and lactococcal phage TP901-1. The X-ray structures of Dit from phages SPP1 (gp19.1) (47), TP901-1 (ORF46 protein) (48), and p2 (ORF15 protein) (49) have been reported, and they were found to share close structural similarities. HHpred also predicted that the ORF71 protein shares structural similarity (98% similarity) with a prophage MUSO2 43-kDa tail protein (PDB 3CDD).…”
Section: Genome Characteristics Of Mycobacteriophagementioning
confidence: 99%
“…128,129 The tail tip complex has different size and morphology in different phages. Phages which use protein receptors for cell binding usually have conical tail tips (e.g., SPP1 130 and λ), whereas phages, using polysaccharide receptors usually have elaborate baseplates at the distal end of the tail (e.g., lactococcal phages TP901-1 6,131 and p2 132,133 ). Furthermore phages usually have side tail fibers or spikes, attached to the periphery of the tail tip complex, as well as a central tail spike.…”
Section: Structure Of the Phage Tailsmentioning
confidence: 99%
“…154 The best studied Siphoviridae baseplates are those of phages p2 and TP901-1 infecting Gram-positive Lactococcus lactis. 131,132 Both these phages use carbohydrate molecules as receptors for attachment to the host. The p2 baseplate (Fig.…”
Section: Structure Of the Phage Tailsmentioning
confidence: 99%
See 1 more Smart Citation